VIP-PERSONNEL FOR TELECOMMUNICATIONS - Yakovishin, Konstantin (Proceedings of National Aviation University (archive), 2014)
In the article the new nonconventional technology of preparation of the experts of high qualification for telecommunications is considered. The experience of teaching of discipline “Informatics” on Faculty of Telecommunication systems in National Aviation University is generalized. The following idea develops: the modern VІР-expert in telecommunications should know and be able to simulate telecommunication systems and protocols in systems of fast designing by methods of the Object- guided programming. In the article the new elements of new technology are considered – they are: the formation of knowledge and skills on modeling the telecommunication protocols, training is exclusively on the examples (projects), teaching of lectures by analogy to a method of descending designing. It is marked, that it is necessary to supplement the usual comments of the texts, photo and video from electronic lectures on a multimedia projector by start and performance of the simulating programs on the computer.